Association between PNPLA2 Gene Polymorphisms and the Risk of Diabetic Kidney Disease in a Chinese Han Population with Type 2 Diabetes - Zhao, Hailing (J Diabetes Res, 2020)
Diabetic kidney disease (DKD) is one of the most common complications of diabetes and the leading cause of end-stage renal disease. Here, we investigated the association of PNPLA2 gene variations with DKD susceptibility in a Chinese Han population. A total of 818 participants with type 2 diabetes were recruited in the case-control study, including 379 patients diagnosed with DKD. We observed that 2 tagSNPs, PNPLA2 rs28633403 (A>G) and rs1138714 (A>G), were associated with DKD (rs28633403: genotype, P = 0.017; allele, P = 0.015; rs1138714: genotype, P = 0.029; allele, P = 0.018). PNPLA2 rs1138693 (T>C), a missense SNP, showed no association with DKD (genotype, P = 0.966; allele, P = 0.845). Genetic model analysis revealed that minor allele G of PNPLA2 rs28633403 was a protective factor of DKD in a dominant model adjusted by confounders (AG+GG vs. AA: adjusted odds ratio (aOR), 0.619; 95% CI 0.447-0.857; P = 0.004) and in an additive model (AG vs. AA: aOR, 0.633; 95% CI 0.447-0.895; P = 0.010; GG vs. AA: aOR, 0.588; 95% CI 0.385-0.897; P = 0.014). Minor allele G of PNPLA2 rs1138714 was associated with a higher risk of DKD in a dominant model adjusted by confounders (AG+GG vs. AA: adjusted odds ratio (aOR), 1.531; 95% CI 1.134-2.067; P = 0.005) and in an additive model (AG vs. AA: aOR, 1.529; 95% CI 1.118-2.091; P = 0.008). The combined effect of PNPLA2 rs28633403 AA+rs1138714 AG or GG genotype showed an association with DKD, adjusted by confounders (aOR, 2.194; 95% CI 1.378-3.492; P = 0.001), which was considered statistically significant with a markedly increased risk of DKD after a Holm-Bonferroni correction for multiple tests (P < 0.00125). Our results suggest that PNPLA2 rs28633403 and rs1138714 are significantly associated with the risk of DKD in a Chinese Han population with type 2 diabetes.